Incidence of fenestration of anterior communicating artery in Indian population using computed tomography angiography - Urvi Sharma; Suman Verma; Subathra Adithan (Wolters Kluwer Medknow Publications, 2023)
Background: Cerebral vasculature fenestration is a rare congenital anomaly and is mostly found in association with aneurysms. Fenestration involving anterior communicating artery (ACoA) is rare. The study's objective was to determine ACoA fenestration incidence in Indian population using computed tomography angiography (CTA). Methodology: Datasets of CT cerebral angiography in 105 patients (67 males and 38 females), of average age- 47.96±16.58 years were systematically reviewed for fenestration in ACoA. The cases with aneurysms and infarcts were excluded from the study. Results: The fenestration involving ACoA was seen in 0.95% (1/105). The fenestration was triangular and located in the proximal part of the artery. No other vascular anomaly was observed in ACoA. Conclusion: The incidence of ACoA fenestration is low in Indian population. Knowledge about the variations of cerebral vasculature will be helpful for radiologists and neurovascular surgeons while dealing with cerebrovascular diseases.